O uso de aceleradores gráficos aplicados ao modelo XcalableMP para a paralelização de algoritmos genéticos - PAZ, Geovani Oliveira Cabral da (2020)
This work aims to present a computational structure of clusters of graphic calipers using a recent distributed memory programming model, XcalableMP. Distributed memory parallel programming often takes advantage of division of computing work among system CPUs, often using message exchange mechanisms such as MPI, but since the discovery and growth of GPU computing new possibilities have also emerged in the sense of To organize machines equipped with GPUs in parallel computing environments, in order to obtain the main advantages of both, mainly in the significant gain of computational performance. Thus, the work developed a cluster architecture of graphic accelerators with the objective of obtaining computational gain in the execution of genetic algorithms. The XcalableMP model was used as the distributed memory process manager, with OpenACC as the GPU programming model forming the entire framework of hybrid programming enablement. The genetic algorithms were executed and tested by untangling the computational performance gain in execution in this structure when compared to the sequential execution in CPU and execution in only one GPU.